NOVEL DAN KOMIK JINGGA DAN SENJA KARYA ESTI KINASIH: KAJIAN STRUKTUR DAN ALIH WAHANA - Tania Intan; Sri Rijati Wardiani (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
This research was conducted to describe the structure of the narrative and transformation from the novel to the comic Jingga and Senja by Esti Kinasih. The research method used is a descriptive-analytical study with the vehicle transfer approach. Data in the form of words, phrases, sentences, and other textual elements were collected by literature study techniques. The data is reviewed with relevant theoretical foundations about the transformation from Damono. The results show that the plot in the comic has decreased the number of sequences because comics only maintain the outline of the story so that it remains logical and easy to understand. The important figures who move the story in the novel are retained in the comics. However, other figures considered not very important were eliminated. The settings used in novels and comics are the same, which is dominated by the class environment. Conversion occurs in the transfer of vehicles so that information is carried more concisely. There are no substitutions, but there are deletions in the number of chapters, the number of pages, and the number of characters in the comics. Improvising occurs in the speech of the characters in the comics to make it more memorable and speak more naturally than in the novel.